2001
DOI: 10.1007/s592-001-8074-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycation of high density lipoproteins on their physicochemical properties and on paraoxonase activity

Abstract: We investigated the effect of incubation of high density lipoprotein (HDL) under hyperglycaemic conditions on lipid composition, physicochemical properties and activity of paraoxonase (PON), a calcium-dependent enzyme associated with HDL that contributes to the antiatherogenicity of this lipoprotein. HDL incubated for three days with various glucose concentrations (0-100 mM) had significant increases in thiobarbituric acid-reactive substances (TBARS) and conjugated dienes with respect to control HDL. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 23 publications
7
71
1
3
Order By: Relevance
“…The individual values of PON1 activity associated to HDL showed a large variability in agreement with our previous studies (3,9,14,15). PON1 activity values in HDL isolated from healthy subjects ranged from 110.2 to 980.1 U/mg and from 26.1 to 276.2 U/mg in obese subjects.…”
Section: Pon Activity and Lipid Hydroperoxide Levels In Lipoproteinssupporting
confidence: 90%
See 1 more Smart Citation
“…The individual values of PON1 activity associated to HDL showed a large variability in agreement with our previous studies (3,9,14,15). PON1 activity values in HDL isolated from healthy subjects ranged from 110.2 to 980.1 U/mg and from 26.1 to 276.2 U/mg in obese subjects.…”
Section: Pon Activity and Lipid Hydroperoxide Levels In Lipoproteinssupporting
confidence: 90%
“…Moreover, previous studies have shown a relationship between PON1 activity and the HDL antioxidant properties (11,12), and it has been demonstrated that HDL with low PON1 activity behave as atherogenic and proinflammatory particles (13). More recently, it has been demonstrated that PON1 activity modulates the susceptibility of HDL to atherogenic modifications induced in vitro such as glycation and homocysteinylation (14,15). Furthermore, using macrophages, it has been demonstrated that PON1 exerts a modulatory role of cholesterol efflux (16), and it has been suggested that PON1 could modulate the interaction between HDL and biological membranes.…”
mentioning
confidence: 97%
“…A practical consequence of this is that formulation of HuPON1 for a use as therapeutics in OP poisoning should include adequate concentration of biocompatible amphiphilic compounds that will preserve the enzyme stability on storage and activity in vivo. In addition, the low specific activity of HuPON1 in serum associated with certain pathologies, such as that reported for diabetes (53)(54)(55), might in fact be due to changes in HDL size and/or shape, which affect the binding affinity and, as a result, stability of the HuPON1 enzyme activity.…”
Section: Structural and Functional Similarities Between Hdl-and Determentioning
confidence: 99%
“…21,22 Multiple risk factors of CVD like hypertension, obesity, diabetes mellitus including abnormal lipids and lipoprotein profile have been associated with psoriasis. Dyslipidemia seems to be related to the severity of psoriasis as it occurs more frequently in patients presenting with large areas of body affected with lesions.…”
Section: Discussionmentioning
confidence: 99%